Older Adults Who Experience Their Lives to Be Completed and No Longer Worth Living: A Systematic Mini-Review Into Used Terminology, Definitions, and Interpretations - Appel, Judith E.; van Wijngaarden, Els J. (Frontiers in Psychology, 2021)
In the Netherlands and in Belgium, a political debate emerged regarding the possibility of euthanasia and assisted suicide (EAS) for older adults who experience their lives as completed and no longer worth living, despite being relatively healthy. This mini-review aimed to (1) present an overview of the terms used to denote this phenomenon as well as their definitions, and to (2) explore how the underlying experiences are interpreted by the study authors. A systematic search was performed in Web of Science, MEDLINE, PsycINFO, and CINAHL, yielding thirty-five articles meeting the selection criteria. We selected empirical, English-language articles published in peer-reviewed journals. Participants had to have a first-person experience of the phenomenon or be assessed for it, or have a third-person experience of the phenomenon. Results show that the terms tiredness of life (ToL) and weariness of life (WoL) were used most frequently, also in the broader literature on suicidal expressions across the lifespan. Many studies mentioned operational definitions or synonyms rather than theoretical definitions. Moreover, inside the EAS debate, the term ToL was more common, its definition incorporated death wishes, and it was regularly framed existentially. Outside of this debate, the phenomenon was generally considered as a part of suicidal ideation distinct from death wishes, and its experience was often associated with underlying psychopathology. We discuss the need to establish consensus definitions and conclude that only a multidimensional view may be suitable to capture the complex nature of the phenomenon.